2019
DOI: 10.1002/jcb.28426
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA DLX6‐AS1 promotes tumor proliferation and metastasis in osteosarcoma through modulating miR‐641/HOXA9 signaling pathway

Abstract: Osteosarcoma (OS) is the most common primary malignant bone tumor. Recently, increasing evidence has shown that the long noncoding RNA (lncRNA) DLX6-AS1 (distal-less homeobox 6 antisense 1) plays significant roles in various types of cancers. However, the functions and underlying mechanisms of DLX6-AS1 have not been explored in OS yet. In this study, we assessed the expression of DLX6-AS1 in OS tissues and cell lines and explored the underlying molecular mechanisms. DLX6-AS1 was found to be significantly upreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 30 publications
2
38
0
Order By: Relevance
“…Previous studies showed that miR-641 served as a tumor suppressor in human lung cancer [17] and induced apoptosis of cervical cancer cells [18]. To study the function of miR-641, we checked its expression and found that miR-641 was apparently downregulated in OS tissues and cells, which was supported by Chen's research [19]. In-depth research showed that miR-641 was negatively regulated by circUBAP2 in OS cells and miR-641 depletion boosted proliferation and invasion of OS cells and promoted the process of EMT.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Previous studies showed that miR-641 served as a tumor suppressor in human lung cancer [17] and induced apoptosis of cervical cancer cells [18]. To study the function of miR-641, we checked its expression and found that miR-641 was apparently downregulated in OS tissues and cells, which was supported by Chen's research [19]. In-depth research showed that miR-641 was negatively regulated by circUBAP2 in OS cells and miR-641 depletion boosted proliferation and invasion of OS cells and promoted the process of EMT.…”
Section: Discussionsupporting
confidence: 56%
“…Human osteoblastic cell line (hFOB1. 19) and OS cell lines (U2OS and SaOS2) were obtained from American Type Culture Collection (ATCC, Manassas, VA, USA). McCoy's 5A medium (Sigma, St Louis, MO, USA), containing 5% CO 2 and 10% fetal bovine serum (FBS) (Sigma), was utilized to culture cells.…”
Section: Samples and Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…A total of 23 articles were identified for full review, 11 of which were excluded due to lack of necessary data or in vitro studies. Finally, the remaining 12 articles [8,9,11,[14][15][16][17][18][19][20][21][22] were included in this meta-analysis. These eligible studies were published between 2017 and 2019, and covered a total of 841 patients.…”
Section: Search Results and Basic Characteristics Of The Included Docmentioning
confidence: 99%
“…This regulation could effectively reverse the inhibitory effects of miRNA-98-5p on the proliferation, migration, invasion, cell cycle and apoptosis of OS cells. Another report showed that distal-less homeobox 6-AS1 could inhibit the proliferation and metastasis of OS cells by targeting the miRNA-641/HOXA9 signaling pathway and acting as a ceRNA ( 32 ). Sun et al ( 33 ), found that MALAT1 could regulate the proliferation and metastasis of OS cells by competitively binding with miRNA-34a/c-5p and miRNA-449a/b.…”
Section: Promotive Role Of Lncrnas In the Occurrence And Development mentioning
confidence: 99%